Effects of Emotion-focused Therapy and Existential Group Therapy on Depression, Anxiety, and Stress in the Victims of Child Sexual Harassment - Behrad Zadafshar; Tayebeh Sharifi; Reza Ahmadi; Maryam Chorami (Iran University of Medical Sciences, 2021)
Background: Traumatic childhood experiences, especially sexual harassment, are among the main factors causing anxiety disorders. The present study aimed to determine the effects of Emotion-focused Therapy (EFT) and Existential Group Therapy (EGT) on depression, anxiety, and stress in the victims of child sexual harassment. Methods: This was a quasi-experimental study with a pre-test-post-test and a control group design. The research population consisted of all men and women with a history of child sexual harassment referring to the counseling and psychological service centers of Isfahan City, Iran. In total, 45 subjects were selected by convenience sampling method and randomly assigned into two experimental groups and a control group (n=15/group). The experimental groups received EFT or EGT (eight 90-minute sessions), Accordingly, the obtained results were compared with the control group immediately after the intervention and 3 months later. The required data were collected by the Depression Anxiety Stress Scales (DASS-42) and analyzed by repeated-measures Analysis of Variance (ANOVA) in SPSS. Results: The current research results revealed that EGT effectively reduced depression symptoms (P<0.01); however, EFT did not significantly affect depression symptoms. Both interventions reduced anxiety symptoms in the study subjects (P<0.01). Furthermore, EFT was more effective than EGT in reducing stress symptoms (P<0.01). There was a significant difference between the pre-test, post-test, and follow-up stages as well as the time*group interaction in the mean scores of depression, anxiety, and stress (P<0.01). Conclusion: Based on the present study findings, psychotherapists and psychiatric nurses are recommended to apply these interventions for controlling depression, stress, and anxiety among the victims of child sexual harassment.